Los procesos de orientación escolar y la toma de decisiones académica y profesional - Fernández García, Carmen María; Peña Calvo, José Vicente; Viñuela Hernández, Mª Paulina; Torío López, Susana (Revista Complutense de Educación, 2007)
Vocational Guidance Processes constitute an instrument which can influence pupils’ academic and vocational preferences. In this paper their importance is compared with other issues such as parents’ opinion, peers’ opinion, etc. The results and expectations included in this work have been elaborated with the information obtained from a sample of 2260 adolescents in their last year of Compulsory Secondary Education in the Principality of Asturias (Spain). The analysis of all this information constitutes the previous theoretical exploration which was necessary for the design of an academic and vocational assessment programme which has been recently published.
Keywords: Vocational Guidance; Academic and Vocational Decisions